Corruption and Income Inequality, Empirical Evidence for Mexico (2010-2020) - Flores Márquez, Héctor; Neme Castillo, Omar; Ríos Bolívar, Humberto (Estudios de Economía, 2023)
Mexico, among the OECD countries, is the country with the greatest difference in income between rich and poor. This situation has been accompanied by high levels of perception of corruption. The goal is to show that corruption and income inequality are correlated. The estimates are affected by the endogeneity problem caused by the two-way causality of corruption and income inequality, and by measurement errors of the variable used for corruption. Therefore, the method of simultaneous equations is used and it is estimated by error-component two stage least squares (EC2SLS), alternatively the Generalized Method of Moments (GMM) and sys-GMM are used, to analyze the sensitivity of the results. Robust evidence is found of a positive relationship between corruption and income inequality in Mexico in the period 2010-2020.